WMC 2018 Senior Problem 32

Algebra Level 3

Let f ( x ) = x 4 + a x 3 + b x 2 + c x + d f\left(x\right)=x^4+ax^3+bx^2+cx+d , where f ( 1 ) = f ( 3 ) = f ( 2 ) = 1 f\left(1\right)=f\left(3\right)=f\left(-2\right)=1 . Also, f ( 1 ) = 0 f\left(-1\right)=0 . Find f ( 0 ) f(0) .

21 4 \frac{21}{4} 9 9 31 4 \frac{31}{4} 1 4 -\frac{1}{4} 25 4 \frac{25}{4}

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Otto Bretscher
Oct 18, 2018

f ( 1 ) = f ( 3 ) = f ( 2 ) = 1 f(1)=f(3)=f(-2)=1 tells us that f ( x ) = ( x 1 ) ( x 3 ) ( x + 2 ) ( x a ) + 1 f(x)=(x-1)(x-3)(x+2)(x-a)+1 for some a a . Now f ( 1 ) = 0 f(-1) =0 gives a = 7 8 a=-\frac{7}{8} so f ( 0 ) = 25 4 f(0)=\boxed{\frac{25}{4}} .

Jordan Cahn
Oct 17, 2018

Plugging in each given value yields an equation in terms of a , b , c , d a, b, c, d : 1 + a + b + c + d = 1 81 + 27 a + 9 b + 3 c + d = 1 16 8 a + 4 b 2 c + d = 1 1 a + b c + d = 0 \begin{aligned} 1 + a + b + c + d &= 1 \\ 81 + 27a + 9b + 3c + d &= 1 \\ 16 - 8a + 4b - 2c + d &= 1 \\ 1 - a + b - c + d &= 0 \end{aligned} Putting these equations into a matrix yields ( 1 1 1 1 0 27 9 3 1 80 8 4 2 1 15 1 1 1 1 1 ) RREF ( 1 0 0 0 9 8 0 1 0 0 27 4 0 0 1 0 13 8 0 0 0 1 25 4 ) \begin{pmatrix} 1 & 1 & 1 & 1 & 0 \\ 27 & 9 & 3 & 1 & -80 \\ -8 & 4 & -2 & 1 & -15 \\ -1 & 1 & -1 & 1 & -1 \end{pmatrix} \xrightarrow{\text{RREF}} \begin{pmatrix} 1 & 0 & 0 & 0 & -\frac{9}{8} \\ 0 & 1 & 0 & 0 & -\frac{27}{4} \\ 0 & 0 & 1 & 0 & \frac{13}{8} \\ 0 & 0 & 0 & 1 & \frac{25}{4} \end{pmatrix} So f ( 0 ) = d = 25 4 f(0) = d = \boxed{\frac{25}{4}} .

I find it easier if you do this:

Let g ( x ) = f ( x ) 1 g(x) = f(x) - 1 , then g ( x ) g(x) has roots 1 , 3 , 2 1,3,-2 . So, g ( x ) = ( x k ) ( x 1 ) ( x 3 ) ( x + 2 ) g(x) = (x-k)(x-1)(x-3)(x+2) for some constant k k . Substitute 0 1 = f ( 1 ) 1 = g ( 1 ) 1 = k = 7 8 0-1 = f(-1) - 1 = g(-1) -1 = \cdots \Rightarrow k = -\frac78 .

Pi Han Goh - 2 years, 7 months ago

Log in to reply

Agreed, this is the intended solution.

Tiger Ang - 2 years, 7 months ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...